Edible films based on native and phosphated 80:20 waxy:normal corn starch - Gutiérrez Carmona, Tomy José (2015)
Edible films based on 80:20 waxy:normal corn starch were evaluated for their potential use in the food industry. Two types of film were prepared by the casting method: The first from native corn starch and the second from starch modified with glycerol. The influence of this chemical modification on the physicochemical and mechanical properties of both the starch and films was investigated. The phosphation of the base material improved the interaction between the plasticizer and the modified starch. This was demonstrated by the lower moisture content and water activity, higher crystallinity, greater elongation under stress and higher thermal resistance observed for the cross-linked films. The results showed that high quality edible films can be prepared from modified 80:20 waxy:normal corn starch, and demonstrated their potential as a coating or packaging material in the food industry.